2009
DOI: 10.1523/jneurosci.5900-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking Upregulates Accumbens mGluR5-Homer2-PI3K Signaling: Functional Implications for Alcoholism

Abstract: The glutamate receptor-associated protein Homer2 regulates alcohol-induced neuroplasticity within the nucleus accumbens (NAC), but the precise intracellular signaling cascades involved are not known. This study examined the role for NAC metabotropic glutamate receptor (mGluR)-Homer2-phosphatidylinositol 3-kinase (PI3K) signaling in regulating excessive alcohol consumption within the context of the scheduled high alcohol consumption (SHAC) model of binge alcohol drinking. Repeated bouts of binge drinking (ϳ1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
337
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(385 citation statements)
references
References 71 publications
(201 reference statements)
42
337
3
Order By: Relevance
“…We further show that rapamycin blocked alcohol-mediated increase in Homer level in the NAc of mice. Our results are in line with Cozzoli et al, showing that Homer expression is elevated in the NAc of mice that experienced alcohol binge drinking (34). Homer plays a key role in the expression of adverse phenotypes associated with exposure to alcohol by modulating glutamate neurotransmission (35).…”
Section: Discussionsupporting
confidence: 93%
“…We further show that rapamycin blocked alcohol-mediated increase in Homer level in the NAc of mice. Our results are in line with Cozzoli et al, showing that Homer expression is elevated in the NAc of mice that experienced alcohol binge drinking (34). Homer plays a key role in the expression of adverse phenotypes associated with exposure to alcohol by modulating glutamate neurotransmission (35).…”
Section: Discussionsupporting
confidence: 93%
“…Congenic mGlu5F1128R knock-in mice (mGlu5 R/R ) were generated as described previously (Cozzoli et al, 2009) and backcrossed at least 5 generations onto the C57BL/6J mice from the University of Texas Southwestern mouse breeding core facility. Congenic Fmr1 KO mice (Dutch-Belgian Fragile X Consortium, 1994) were bred on the C57BL/6J background.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether a specific disruption in mGlu5-Homer is sufficient to mimic known phenotypes of Fmr1 KO mice, we examined an mGlu5 knock-in mouse with a point mutation (F1128R) in the C-terminal, intracellular Homer-binding site (mGlu5 R/R ) (Tu et al, 1998;Cozzoli et al, 2009). We first confirmed that the mGlu5 R/R mice had reduced Homer interactions with mGlu5 and determined whether Homer interactions with other known Homer binding proteins were affected.…”
Section: Mglu5f1128r Knock-in Mice Have a Selective Disruption Of Gromentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic EtOH intake has also been shown to enhance intracellular signaling associated with mGluRs, particularly mGluR5, in the nucleus accumbens (NAc) (Cozzoli et al 2009). While chronic EtOH drinking can induce increases in mGluR1 and mGluR5 protein expression in NAc and amygdala (Szumlinski et al 2008;Obara et al 2009), changes in mGluR5 signaling in NAc are not always associated with an increase in the protein itself (Szumlinski et al 2008).…”
Section: Chronic Ethanol Effects On Glutamatergic Transmission and Glmentioning
confidence: 99%